1999
DOI: 10.1074/jbc.274.11.7467
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Inositol 1,4,5-Trisphosphate Receptor by Cyclic Nucleotide-dependent Kinases in Vitroand in Rat Cerebellar Slices in Situ

Abstract: Activation of intracellular signal transduction cascades frequently involves increased phosphoinositide hydrolysis following stimulation of phospholipase C. Inositol 1,4,5-trisphosphate (IP 3 ), 1 a second messenger produced by phosphoinositide hydrolysis, mediates Ca 2ϩ release from intracellular stores by binding to IP 3 -sensitive Ca 2ϩ channels, thereby increasing their "open" probability (1). IP 3 receptors derive from at least three different genes, constituting types I, II, and III, which are approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 54 publications
2
81
1
1
Order By: Relevance
“…A cGK-dependent inhibition of InsP 3 production has been described in permeabilized gastric smooth muscle cells (34) and in transfected CHO cells (37). Furthermore, a direct phosphorylation of the InsP 3 receptor by cGKI has been demonstrated in vitro and in vivo (38,39). Finally, an increased reuptake of calcium ions into sarcoplasmatic stores achieved by cGK-dependent activation of sarcoplasmatic Ca 2ϩ -ATPase pumps has been demonstrated in vascular smooth muscle (40 -42).…”
Section: Discussionmentioning
confidence: 96%
“…A cGK-dependent inhibition of InsP 3 production has been described in permeabilized gastric smooth muscle cells (34) and in transfected CHO cells (37). Furthermore, a direct phosphorylation of the InsP 3 receptor by cGKI has been demonstrated in vitro and in vivo (38,39). Finally, an increased reuptake of calcium ions into sarcoplasmatic stores achieved by cGK-dependent activation of sarcoplasmatic Ca 2ϩ -ATPase pumps has been demonstrated in vascular smooth muscle (40 -42).…”
Section: Discussionmentioning
confidence: 96%
“…Although an extra- cellular gradient of membrane-permeant cAMP analogs was shown to induce growth cone attraction (Gundersen and Barrett, 1980;Lohof et al, 1992), these reports did not examine other signaling components, e.g., calcium signaling. Recent studies indicated that multiple levels of interactions between Ca 2ϩ and cAMP pathways exist (Eliot et al, 1993;Cooper et al, 1995;Wayman et al, 1995;Mons et al, 1998;Haug et al, 1999;Gorbunova and Spitzer, 2002). Therefore, it was not clear whether growth cone attraction induced by extracellular gradients of cAMP analogs was mediated directly by intracellular cAMP signals or by other pathways affected by cAMP (e.g., Ca 2ϩ ).…”
Section: Discussionmentioning
confidence: 98%
“…Early investigations using extracellular gradients of membrane-permeant cAMP analogs suggested that the cAMP pathway could influence the direction of growth cone extension (Gundersen and Barrett, 1980;Lohof et al, 1992). However, because Ca 2ϩ -and cAMP-signaling pathways interact (Eliot et al, 1993;Cooper et al, 1995;Wayman et al, 1995;Mons et al, 1998;Haug et al, 1999;Gorbunova and Spitzer, 2002), gradients of cAMP analogs could potentially activate Ca 2ϩ or other signaling pathways to elicit growth cone attraction. Conclusive and direct evidence for local cAMP signals to directly mediate growth cone turning remain to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal InsP 3 R1 is one of the major substrates of PKA phosphorylation in the brain (29,30). PKA phosphorylates InsP 3 R1 at two sites, Ser-1589 and Ser-1755 (31)(32)(33)(34)(35)(36). PKA phosphorylation activates InsP 3 R1 by increasing the sensitivity of InsP 3 R1 to activation by InsP 3 (35,(37)(38)(39).…”
Section: From the Department Of Physiology University Of Texas Southmentioning
confidence: 99%